Liderança movida pelo propósito - Gomes, Fabiano Defferrari (Universidade do Vale do Rio dos Sinos, 2018)
This paper aims to understand the role of leadership in the purpose-driven companies from the perception of leaders of strategic positions and led of these organizations. The study was carried out using qualitative exploratory research through 22 semi-structured interviews, of which 11 were leaders in strategic rolls and 11 were led from 12 profit-making companies considered to be purposeful, located in Brazil, namely Rio Grande do Sul and São Paulo. For the data treatment, the content analysis was adopted with the help of the NVIVO 11 software. From the theory, the interview script was constructed and 11 categories were defined, from which 52 subcategories emerged in the analysis. The primary results of each category were: 1) there is no separation of personal and professional values. 2) The connection between the business purpose and the people happens with excellent communication and more horizontal relations. 3) Leadership driven by the spirit is centered on the human being and conveys the congruence between discourse and practice. 4) Leadership values push the limits of the company and positively impact society. 5) Plurality is built in safe, collaborative and trustworthy environments. 6) Freedom with accountability is an essential part of building purposeful business leadership. 7) Reciprocity is built with feedback acculturation and real attitudes. 8) Purpose-driven leadership is willing to sacrifice profits in the short run to preserve the company's purpose, values, and uniqueness. 9) The contexts and environments, formal and informal in which people meet, generate and reinforce the connections and affinities between people. 10) The most significant challenges are related to leadership skills such as communication, human relations, coherence, and evolution. 11) Knowing yourself, values, and purpose is key to developing leadership. The paradigm of leadership driven by purpose always has happiness within the equation. Values are not negotiated, even if this means slower growth for the organization.
Keywords: Liderança; Propósito; Valores; Organizações movidas pelo propósito; Leadership; Purpose; Values; Purpose-driven organizations; ACCNPQ::Ciências Sociais Aplicadas::Administração